Feedlot performance and carcass yield of Hararghe Highland (Bos indicus) bulls using different concentrate feeds - Tsegay Teklebrhan Gebremariam (Acta Scientiarum. Animal Sciences, 2018)
A study was conducted to evaluate the feedlot performance and carcass yield of Hararghe Highland bull using different types of concentrate feeds fed grass hay as a basal diet in eastern Ethiopia. Thirty Hararghe Highland bulls were blocked by weight and randomly allocated to one of the following six treatments. T1 = Hay ad libitum + 4kg dried cafeteria leftover; T2 = Hay ad libitum + 4kg wheat bran; T3 = Hay ad libitum + 4 kg d-1 maize grain; T4 = Hay ad libitum + 4kg d-1 mix (1:1, wheat bran to maize grain, respectively); T5 = Hay ad libitum + 4kg scrambled whole groundnut; T6 = Hay ad libitum + 4kg d-1 mix (equal proportion of maize grain, wheat bran, dried cafeteria leftover and scrambled whole groundnut. Bulls were fed for 90 days and slaughtered for carcass yield studies. Bulls fed on T6 and T3 had highest (p < 0.05) finished weight and ADG than did in T2, T5 and T1. Similarly, better (p < 0.05) gain to feed ratio was noted on bulls fed T6 and T3 than rest of treatments. Carcass yield on slaughter weight was also improved in T6 and T3 consistent to feedlot performance traits. Bulls supplemented with T6 and T3 had highest carcass yield than T2, T5, T1 and T4. Therefore, this study suggested that Hararghe Highland bull has potent for feedlot industry using strategic supplementation.